2017
DOI: 10.1080/14728222.2017.1353603
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances and severe stress as glial activators: key targets for treating central sensitization in chronic pain patients?

Abstract: The mechanism of sensitization of the central nervous system partly explains the chronic pain experience in many patients, but the etiological mechanisms of this central nervous system dysfunction are poorly understood. Recently, an increasing number of studies suggest that aberrant glial activation takes part in the establishment and/or maintenance of central sensitization. Areas covered: This review focused on preclinical work and mostly on the neurobiochemistry studied in animals, with limited human studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 123 publications
2
66
0
1
Order By: Relevance
“…Regression analysis in the current study found trait anxiety to be a predictor of CSI scores in people with NSCLBP, reflective of the tendency of high trait anxious individuals to react to threats with state anxiety. State anxiety is a stress response, and chronic stress has been identified in animal work as an activator of glial cells in the central nervous system, which may be associated with neuroinflammation and subsequent CS onset or aggravation . It is suggested that discomfort experienced by sensory under‐ or overstimulation constitutes stressors, which leads to a stress response .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regression analysis in the current study found trait anxiety to be a predictor of CSI scores in people with NSCLBP, reflective of the tendency of high trait anxious individuals to react to threats with state anxiety. State anxiety is a stress response, and chronic stress has been identified in animal work as an activator of glial cells in the central nervous system, which may be associated with neuroinflammation and subsequent CS onset or aggravation . It is suggested that discomfort experienced by sensory under‐ or overstimulation constitutes stressors, which leads to a stress response .…”
Section: Discussionmentioning
confidence: 99%
“…State anxiety is a stress response, and chronic stress has been identified in animal work as an activator of glial cells in the central nervous system, which may be associated with neuroinflammation and subsequent CS onset or aggravation. 50 It is suggested that discomfort experienced by sensory under-or overstimulation 13,51 constitutes stressors, which leads to a stress response. 13,47 Physiological changes occur in the central nervous system in response to stressors, including those associated with autonomic arousal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stress and physical (in)activity, other lifestyle factors such as sleep are often neglected by clinicians working with people with chronic pain. Insomnia/sleep disturbances constitutes an important example of physiological stressor .…”
Section: Stress In People With Chronic Painmentioning
confidence: 99%
“…Indeed, recent studies have linked severe stress to specific immune activation (Beurel and Lowell ) and glial activation (Nijs et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, the immune system of rhesus monkeys is more similar to humans than the immune systems of rodents, making monkeys the best choice for evaluating and correlating immunologic responses and CNS disease. Indeed, recent studies have linked severe stress to specific immune activation (Beurel and Lowell 2017) and glial activation (Nijs et al 2017).…”
Section: Introductionmentioning
confidence: 99%